Test–retest reliability of the SVO-Slider Measure and other psychometric measures of personality traits - Debora Frei; Stefan Wehrli; Alexander Ehlert; Fabian Winter; Heiko Rauhut (Judgment and Decision Making)
This study presents findings from a 4-year panel study examining three major questions regarding the measurement of social value orientation (SVO). First, we investigate the test–retest reliability of the Slider Measure (SLM, Murphy et al., 2014) over a period of up to 4 years in a large, demographically diverse sample. Second, we compare the stability of the SLM to related measurements of prosociality and distributional preferences along the behavior–behavioral tendency–trait continuum, including single behaviors (e.g., the Dictator Game and the Prisoner’s Dilemma), alternative behavioral tendencies (e.g., survey-based measures of altruism), and broader personality traits (e.g., Big-Five, HEXACO, Dark Factor D). Third, we explore differences in individual trajectories of SVO, focusing on how age and gender influence its stability and change over time. Our study thus complements earlier research on the stability of the SLM by extending the time period and depth of analysis, and putting the measure in the context of other related measures. The results show a considerable degree of stability, higher than all behavioral games, but often lower than fully fledged measures of personality traits. Furthermore, we find that age has a stabilizing effect on behavior in the SLM. With regard to gender, we find that women behave generally more prosocial than men but that they do not differ in their stability. We conclude that the SLM is a suitable method for assessing individual SVO over longer time periods and is best thought of as covering a sweet spot between stable personality traits and immediate behavioral expressions.